1997
DOI: 10.1038/sj.onc.1201481
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutation of RET codon 883 in two cases of de novo MEN 2B

Abstract: Germline mutations in the RET proto-oncogene are seen in the majority of patients with the dominantly inherited cancer syndromes multiple endocrine neoplasia type 2 (MEN 2). The clinical subtypes of MEN 2 (MEN 2A, MEN 2B and familial MTC) all have medullary thyroid carcinoma, but vary in the involvement of pheochromocytoma, parathyroid adenoma/hyperplasia and developmental abnormalities. A single RET mutation, resulting in the substitution M918T, has been identi®ed in 94% of cases of MEN 2B (which consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(84 citation statements)
references
References 27 publications
0
81
0
3
Order By: Relevance
“…The MEN2A mutations were identified primarily in cysteine residues of the RET extracellular domain that lead to ligandindependent RET dimerization via the formation of an intermolecular disulfide bond (Asai et al, 1995;Santoro et al, 1995;Eng, 1999). The MEN2B mutations, characterized by a methionine-to-threonine change at codon 918 or an alanine-to-phenylalanine change at codon 883 in the tyrosine kinase domain, result in an increase of intrinsic RET catalytic activity (Carlson et al, 1994;Gimm et al, 1997;Smith et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The MEN2A mutations were identified primarily in cysteine residues of the RET extracellular domain that lead to ligandindependent RET dimerization via the formation of an intermolecular disulfide bond (Asai et al, 1995;Santoro et al, 1995;Eng, 1999). The MEN2B mutations, characterized by a methionine-to-threonine change at codon 918 or an alanine-to-phenylalanine change at codon 883 in the tyrosine kinase domain, result in an increase of intrinsic RET catalytic activity (Carlson et al, 1994;Gimm et al, 1997;Smith et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…MEN2B patients possess mutations that cluster within the tyrosine kinase domain, most commonly a methionine-to-threonine substitution (M918T) and, less frequently, mutations such as A883F or V804M and Y806C/S904C (Carlson et al 1994b;Eng et al 1994;Hofstra et al 1994;Smith et al 1997;Miyauchi et al 1999;Menko et al 2002). Sporadic MTC and papillary thyroid carcinoma also display dominant activating Ret mutations (Grieco et al 1990;Bongarzone et al 1994;Chiefari et al 1998;Scurini et al 1998).…”
mentioning
confidence: 99%
“…11) In MEN 2B, approximately 95% of families have an M918T germline mutation in exon 16, [12][13][14] and recent research revealed A883F and V804M with Y806C germline mutation as another cause of MEN 2B. [15][16][17] Germline mutations in RET have been found in 88% of FMTC families, and the majority of mutations in FMTC occur in the same five cysteine codons altered in MEN 2A.10) C630F, C630Y, E768D, L790F, Y791F, V804L, V804M and S891A germline mutations have been found in some FMTC families. 11,[18][19][20][21][22][23] Various somatic mutations in the cysteine-rich domain and tyrosine kinase domain of RET have been identified in sporadic MTCs.…”
mentioning
confidence: 99%
“…11) In MEN 2B, approximately 95% of families have an M918T germline mutation in exon 16, [12][13][14] and recent research revealed A883F and V804M with Y806C germline mutation as another cause of MEN 2B. [15][16][17] Germline mutations in RET have been found in 88% of FMTC families, and the majority of mutations in FMTC occur in the same five cysteine codons altered in MEN 2A.…”
mentioning
confidence: 99%